2019
DOI: 10.1186/s12888-019-2215-3
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the acceptability of cognitive bias modification for paranoia (CBM-pa) in patients with psychosis

Abstract: Background: Cognitive Bias Modification (CBM) has been used successfully as a computer-based intervention in disorders such as anxiety. However, CBM to modify interpretations of ambiguous information relevant to paranoia has not yet been tested. We conducted a qualitative investigation of a novel intervention called CBM for paranoia (CBM-pa) to examine its acceptability in patients with psychosis. Methods: Eight participants with psychosis who completed CBM-pa were identified by purposive sampling and invited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…Given CBMs low face validity, both groups expressed a desire to better understand how CBM training works and how doing the training may help reduce alcohol use and improve social anxiety. This echoes the feedback provided in previous CBM acceptability studies (Beard et al, 2012; Leung et al, 2019). Provision of a compelling rationale at the outset of the program is important for initial buy‐in and setting expectations about the purpose and nature of the intervention (e.g., computerized, repetitive training; Beard and Peckham, 2020).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Given CBMs low face validity, both groups expressed a desire to better understand how CBM training works and how doing the training may help reduce alcohol use and improve social anxiety. This echoes the feedback provided in previous CBM acceptability studies (Beard et al, 2012; Leung et al, 2019). Provision of a compelling rationale at the outset of the program is important for initial buy‐in and setting expectations about the purpose and nature of the intervention (e.g., computerized, repetitive training; Beard and Peckham, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…have potential utility for service providers and emerging adults alike. Consistent with prior research on the acceptability of CBM (Beard et al, 2019;Leung et al, 2019), responses from both groups were generally positive, with most participants describing the beta intervention as easy to complete and straightforward. Emerging adults rated the usability of the program more positively than did the service providers, with ratings equivalent to "B-grade" (M = 74.0) and "Cgrade" (M = 68.4), respectively.…”
Section: Principal Findingssupporting
confidence: 79%
See 1 more Smart Citation
“…In line with this, a study was conducted to evaluate the acceptability of a beta version of the Re-train Your Brain program according to the perspectives of clinicians and emerging adults with hazardous drinking and heightened social anxiety [ 51 ]. The results indicated that the ApBM+IBM intervention was an acceptable adjunct to traditional evidence-based treatments with potential clinical utility, a finding that mirrors previous CBM acceptability studies [ 52 , 53 ]. To enhance engagement, clinical utility, and intrinsic motivation to complete the training, clinicians and emerging adults suggested that the program should include a psychoeducational and motivation enhancement-type module before the first training session.…”
Section: Introductionsupporting
confidence: 75%
“…The eleven primary studies were conducted in different countries. In the United States of America, there were three articles (Barut et al., 2016; Blakeman et al., 2013; Jenkins & Carpenter‐Song, 2009), followed by two in each of the United Kingdom (Kaar et al., 2019; Leung et al., 2019) and South Africa (Nxumalo Ngubane et al., 2019; de Wet et al., 2015), then one study in each country: Australia (Henderson & Cock, 2015), Poland (Nowak et al., 2017), Israel (Mazor & Doron, 2011) and Spain (Saavedra, 2009).…”
Section: Resultsmentioning
confidence: 99%